On (missing) links between German, Latin American, and French Mediatization Research: Reflections on Diverse Research Milieus and Their Traditions - Averbeck-Lietz , Stefanie (MATRIZes, 2023)
Mediatization research is no European invention, being also rooted in Latin American Cultural Studies and semiotics. Building on an analytical scheme on how to analyze the history of a study field in communication research in terms of its corpus of ideas and its social corpus, this article discusses the transnational (dis-)connections in the field of mediatization research regarding a) the Latin American and French roots of this research field and b) by trying to answer why they are still so unknown, at least in German communication studies. Still today, E. Verón, Martín-Barbero, A. Mattelart, and others are more or less unknown authors in German communication studies.